Fresh breeze cuts down one-third ventilation rate of a natural draft dry cooling tower: A hot state modelling - Wang, Weiliang; Wang, Yuzhao; Hai Zhang; Lin, Guanming; Lu, Junfu; Yue, Guangxi; Ni, Weidou (Applied thermal engineering, 2018)
The natural draft dry cooling tower (NDDCT) has been increasingly used in power generation for its merits of excellent water-saving, high energy saving, simple maintenance and long life service. To study the performance of a newly installed 660 MW NDDCT under crosswind condition, a model with scale of 1:200 was built according to the scaling law of geometric similarity. The experiments were set up in self-similar region with high Reynolds to meet momentum similarity, while meeting the scaling law of Froude and Euler numbers. A first order law radiator resistance model is also proposed and verified by a systematic test. The exponent law profile of wind velocity above the ground was built and verified by experimental data. On the ground of a constant heating rate bases, the flow field inside the NDDCT and the ventilation rate were investigated at the crosswind range of 0–20 m/s.